Encourage Students Creativity Through Creative Science Learning Activities on Environmental Issues - Selvies L Babutta; R Riandi; Ida Kaniawati; Sumar Hendayana (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study provides an overview of science creativity learning activities using online learning media as a stimulus and describes creative competence, which includes the development of curiosity, creative thinking, and students' creative products on the theme of environmental sustainability. Data collection is done by observation and analyzed based on the phenomena that arise in learning, which are divided into four criteria. Based on the results of the study, it was found that creativity learning activities that were stimulated using online learning media and carried out through eight learning steps gave a positive response to student creativity. The development of students' curiosity and creative thinking is in a good category but needs improvement, especially in terms of giving critical comments on products Assessment of students' creative products shows that the characteristics of creativity are very good. This study recommends the need to integrate a combination of various online learning media to be able to enrich the learning process of creativity in science learning with students' creative products in the form of ideas, pictures, charts, objects, and prototypes in order to motivate students to be more creative, think critically, and actively participate in protecting the earth in a sustainable way.